On the expansion of biological functions of lytic polysaccharide monooxygenases. Issue 6 (8th January 2022) - Vandhana, Theruvothu Madathil; Reyre, Jean‐Lou; Sushmaa, Dangudubiyyam; Berrin, Jean‐Guy; Bissaro, Bastien; Madhuprakash, Jogi
Summary: Lytic polysaccharide monooxygenases (LPMOs) constitute an enigmatic class of enzymes, the discovery of which has opened up a new arena of riveting research. LPMOs can oxidatively cleave the glycosidic bonds found in carbohydrate polymers enabling the depolymerisation of recalcitrant biomasses, such as cellulose or chitin. While most studies have so far mainly explored the role of LPMOs in a (plant) biomass conversion context, alternative roles and paradigms begin to emerge. In the present review, we propose a historical perspective of LPMO research providing a succinct overview of the major achievements of LPMO research over the past decade. This journey through LPMOs landscape leads us to dive into the emerging biological functions of LPMOs and LPMO‐like proteins. We notably highlight roles in fungal and oomycete plant pathogenesis (e.g. potato late blight), but also in mutualistic/commensalism symbiosis (e.g. ectomycorrhizae). We further present the potential importance of LPMOs in other microbial pathogenesis including diseases caused by bacteria (e.g. pneumonia), fungi (e.g. human meningitis), oomycetes and viruses (e.g. entomopox), as well as in (micro)organism development (including several plant pests). Our assessment of the literature leads to the formulation of outstanding questions, promising for the coming years exciting research and discoveries on these moonlighting proteins.